Perbaikan Tegangan dengan Menggunakan Kapasitor Bank 25 MVAR pada Gardu Induk Banda Aceh - Suriadi; Azmi, Saddam; Gapy, Mansur; Ali, Masri; Arhami; Ibrahim, Masri; Suhaeri; Nasution, Elvy Sahnur (Yayasan Kawanad, 2023)
The Nagan Raya coal-fired power plant in Aceh, Indonesia, serves as a major supplier of electricity to the region's power grid. However, the power generation unit of the plant, which supplies reactive power to the subsystem, often experiences disturbances that cause voltage values in the Banda Aceh substation system to decrease. This decrease in voltage can be detrimental to the quality of power supplied to the consumers. To address this issue, a capacitor bank with a capacity of 25 Mvar was installed at the end of 2016. The capacitor bank was successful in increasing the voltage value at the substation and proved to be an effective solution. However, with the anticipated growth in load in the coming years and the possibility of future disturbances in the power generation unit, it has been proposed that an additional capacitor bank unit with the same capacity be installed to further enhance the voltage quality at the Banda Aceh substation. To assess the feasibility of this proposal, simulations were carried out using ETAP 12.6.0 software. The simulation results show that the addition of a 25 Mvar capacitor bank unit would lead to an increase in the substation voltage value of around 5-6 KV. This increase in voltage would help to maintain the quality of power supplied to the consumers and ensure that the power grid remains stable even in the event of disturbances in the power generation unit. Overall, the proposed installation of an additional capacitor bank unit would be a cost-effective solution to enhance the voltage quality at the Banda Aceh substation and ensure the stability of the power grid. This solution could be adopted by other power plants facing similar issues in maintaining voltage quality in their power grid systems.